2014
DOI: 10.1589/jpts.26.1493
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy for Women with Stress Urinary Incontinence: A Review Article

Abstract: [Purpose] This review article is designed to expose physiotherapists to a physiotherapy assessment of stress urinary incontinence (SUI) and the treatment and possibly preventive roles that they might play for women with SUI. Specifically, the goal of this article is to provide an understanding of pelvic floor muscle function and the implications that this function has for physiotherapy treatment by reviewing articles published in this area. [Methods] A range of databases was searched to identify articles that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 56 publications
0
43
1
5
Order By: Relevance
“…These changes are also responsible for negative repercussions on the pelvic floor complex, which are aggravated by prior history of traumatic and obstetric injury13 ) . Age seems to be the primary cause of urinary disorders, causing decreases in collagen fibers, declines in bladder capacity and low postmenopausal estrogen levels14,15,16 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes are also responsible for negative repercussions on the pelvic floor complex, which are aggravated by prior history of traumatic and obstetric injury13 ) . Age seems to be the primary cause of urinary disorders, causing decreases in collagen fibers, declines in bladder capacity and low postmenopausal estrogen levels14,15,16 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Age-related urinary changes, such as urinary incontinence, often lead to severe psychosocial problems that have a negative effect on the quality of life of women8, 9, 16 ) . This study found that the perimenopausal period exerted a greater impact on quality of life in relation to urinary losses.…”
Section: Discussionmentioning
confidence: 99%
“…4 El ejercicio físico rehabilitador se ha convertido en parte del tratamiento clínico de la IU. 5 La terapia conservadora es la primera línea en la recomendaciones clínicas en el manejo de la IU, 3,6 específicamente la rehabilitación a través del entrenamiento de la musculatura del suelo pélvico tanto para la IU de esfuerzo, de urgencia o mixta. 7 Como alternativa al entrenamiento específico de la musculatura del suelo pélvico, se encuentran diferentes terapias con ejercicio físico que aun cuentan con poca evidencia en la rehabilitación de la IU.…”
Section: La Incontinencia Urinaria (Iu) Es Definida Por La Sociedad Iunclassified
“…56 Pelvic floor muscle training (PFMT, also known as Kegel Exercises), vaginal cones, neurostimulation, biofeedback, magnetic therapy and electrical stimulation are varieties of physical therapies used in the management of female UI.…”
Section: Physiotherapymentioning
confidence: 99%